Influence of dermal exposure to ultraviolet radiation and coal tar (polycyclic aromatic hydrocarbons) on the skin aging process - Borska, Lenka; Andrys, Ctirad; Krejsek, Jan; Palicka, Vladimir; Vorisek, Viktor; Hamakova, Kvetoslava; Kremlacek, Jan; Borsky, Pavel; Fiala, Zdenek (Journal of dermatological science, 2016)
BACKGROUND: Ultraviolet radiation (UVR) and crude coal tar (CCT) containing PAHs can accelerate the skin-aging process (SAP). However, UVR induces the formation of an important protective factor in SAP (vitamin D). OBJECTIVE: To determine the relation of SAP to selected risks and benefits of combined dermal exposure to UVR and coal tar (PAHs). METHODS: The study group consisted of patients with chronic stable plaque psoriasis and treated by Goeckerman therapy (GT; daily dermal application of UVR and 5% CCT ointment). The levels of urinary 1-hydroxypyrene (1-OHP), oxidative stress (DNA and RNA damage), genotoxic damage (chromosomal aberration in peripheral lymphocytes; ABC), 25-hydroxy-vitamin D [25(OH)D] and the PASI score were evaluated before and after GT. RESULTS: Intensive dermal absorption of PAHs was confirmed by increased levels of 1-OHP (p<0.01). After the therapy, we found an increased level of oxidative stress (p<0.05), an increased level of genotoxic damage (ABC; p<0.001), a high efficiency of the treatment (p<0.001) and an elevated production of 25(OH)D (p<0.01). We also found a relationship between the duration of UVR and the genotoxic damage (p<0.01), vitD (p<0.05) and the PASI score (p<0.05). Furthermore, we found a relationship between oxidative stress and 25(OH)D (p<0.05) and between genotoxic damage and the PASI score (p<0.05). CONCLUSION: Dermal exposure to UVR and coal tar (PAHs) enhances the level of oxidative stress and genotoxic damage and thus contributes to SAP. However, the exposure is very effective as a treatment and elevates the production of 25(OH)D, the protective factor in SAP. According to our results, UVR is probably a more hazardous factor in SAP.
Keywords: výsledek terapie; kombinovaná terapie; Young Adult; oxidační stres; poškození DNA; Male; biologické markery; Combined Modality Therapy; Middle Aged; Skin Aging; Oxidative stress; DNA Damage; psoriáza; mladý dospělý; Biomarkers; Pyrenes; Ultraviolet Therapy; aplikace kožní; dehet uhelný; stabilita RNA; chronická nemoc; Adult; pyreny; Aged; dospělí; mužské pohlaví; senioři; Polycyclic aromatic hydrocarbons; Chronic Disease; vitamin D; Smoking; polycyklické aromatické uhlovodíky; terapie ultrafialovými paprsky; keratolytika; Chromosomal aberration; Treatment Outcome; Time Factors; Keratolytic Agents; stárnutí kůže; lidé; Psoriasis; ženské pohlaví; Humans; 25-Hydroxy vitamin D; RNA Stability; časové faktory; celotělové ozáření; UV radiation; Vitamin D; Female; Oxidative Stress; Whole-Body Irradiation; lidé středního věku; kouření; Polycyclic Aromatic Hydrocarbons; Coal Tar; Administration, Cutaneous